COMPARISON OF MODERN AND TRADITIONAL MARKETS FOR VEGETABLE COMMODITIES (Olericu lture) (CASE STUDY: LOTTE AND PA’BANG BAENG) - azisah; Ali, M Saleh; Mujahid, imam; Latief, Rindam (International Journal of Psychosocial Rehabilitation, 2020)
The difference between traditional markets and modern markets which have inversely proportional characteristics is considered to weaken the position of traditional markets. The existence of unclear rules or regulations from the government regarding the modern market industry, especially regarding the distance between market locations, including cleanliness adds to the effort to handle traditional markets. The scope of Comparison of traditional markets and modern markets in this study includes Product, Price, Location and Distribution Channels indeed at least influences traditional markets, but specifically for fresh commodities such as vegetables, traditional markets still have their own market share. Consumers who buy in modern markets also buy in traditional markets and this is not limited to the level or economic class of consumers. However, it still requires a lot of energy to reduce and find solutions to the striking differences between traditional and modern markets. The most likely strategy used by traditional markets is how to establish synergies with modern markets, not by facing each other to attack each other.